The missing link? The role of sub-national governance in transnational social protections. (2nd January 2017) - Dobbs, Erica; Levitt, Peggy
Abstract: Much of the existing literature on social protection for immigrants focuses on what people do as individuals and households or on national policy. However, there is a third set of actors which deserves attention: sub-national and local governments. Drawing comparisons both within and between the United States and Spain, this article analyzes the extent to which sub-national governments step in when national policies block immigrant access to healthcare. Using cross-national surveys, national and sub-national data, we find that sub-national governments often provide some level of social protection, even in the case of undocumented immigrants. However, their responses vary significantly and are not easily explained by left-right political divides, changes in levels of diversity, or the relative political power of immigrants. Future work is needed not only to explain variations in non-citizen health coverage policies at the sub-national level in receiving countries, but also to offer a more complete picture of immigrant resource environments through a parallel analysis of sending-state social protection policies.